2015
DOI: 10.15233/gfz.2015.32.12
|View full text |Cite
|
Sign up to set email alerts
|

Influences of outdoor meteorological conditions on indoor wintertime short-term PM1 levels

Abstract: We investigated the relationship between wintertime 1-min mean urban indoor particulate matter mass concentrations for particles with aerodynamic diameter of < 1 µm (PM 1 ) and outdoor atmospheric conditions. Particle concentrations were measured by two light-scattering laser photometers. Aerosol monitors were placed in the ground and first floor corridors of an university building, with inlets at heights of 1.7 m above the floor. The building is located in residential area of Zagreb, Croatia. During the exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The results of Chan's research were partially confirmed by Klaic et al [43],who studied winter correlations between the spread of PM 1.0 dust indoors and outside weather conditions in Zagreb. Xu et al [44] showed a decrease in PM 1 with a simultaneous increase in outdoor temperature, rainfall and horizontal wind speed, as well as an increase in indoor PM 1.0 concentration with increasing relative humidity outside the building.…”
Section: Influence Of Meteorological and Building Parameters On The Level Of Indoor Dust Pollutionmentioning
confidence: 62%
See 1 more Smart Citation
“…The results of Chan's research were partially confirmed by Klaic et al [43],who studied winter correlations between the spread of PM 1.0 dust indoors and outside weather conditions in Zagreb. Xu et al [44] showed a decrease in PM 1 with a simultaneous increase in outdoor temperature, rainfall and horizontal wind speed, as well as an increase in indoor PM 1.0 concentration with increasing relative humidity outside the building.…”
Section: Influence Of Meteorological and Building Parameters On The Level Of Indoor Dust Pollutionmentioning
confidence: 62%
“…A different look at the existing correlations between the PM concentration in interiors and meteorological parameters is presented by a team of Iranian researchers in the article by Nadali et al [11]. They built, like Klaic et al [43], a symmetric linear correlation matrix in which they analysed the possibilities of correlation of C in concentration with air temperature and relative humidity, as well as wind speed. Since these newer results were based on a large number of buildings and because they partially contradict earlier results, it is worth mentioning that the correlation coefficients (r) between the PM concentration in the interior and the parameters were as follows: With temperature the correlation is negative; with relative air humidity, however, the correlation is r = 0.07, which means that no significant relationship was observed between the concentrations of solid particles and air humidity.…”
Section: Influence Of Meteorological and Building Parameters On The Level Of Indoor Dust Pollutionmentioning
confidence: 99%
“…However, it is well-known that the observed wind speed at Senj station should be considerably larger. This issue has previously been addressed by Bencetić Klaić et al (2009), who show that the location of the observational station is shielded from the Bora directions and therefore underestimates the Bora wind speed. The wind speed observed at the station is underestimated by about 40%, but the wind direction is realistic.…”
Section: Bora and Siroccomentioning
confidence: 91%
“…Before the start of the fi rst set of sawing, the measuring devices were calibrated (the mass concentration of particles in the air before the start of sawing). Prior to analysis, the concentration of PM was obtained photometrically and was corrected by using the correction formula when compared with the gravimetric data as described by Bencetic Klaic et al 11 .…”
Section: Methodsmentioning
confidence: 99%